Kinetics and Equilibrium Properties of Fe(II) Adsorption Using Modified Empty Palm Oil Bunches Activated Carbon - Khairahma; Ramadhan, Dwi Sapri; Faradilla, Putri; Rahmah, Siti; Selly, Rini; Jasmidi; Zubir, Moondra (Universitas Negeri Medan, 2025)
The increasing palm oil production in Indonesia contributes to higher agricultural waste, particularly Empty Fruit Bunches (EFB). This waste can be processed into activated carbon as an adsorbent to remove Fe(II) ions from Palm Oil Mill Effluent (POME). This study reviews two EFB-based adsorbents: Fe-Cu modified activated carbon and a composite of activated carbon with Copper-TAC Metal Organic Frameworks (Cu(TAC)₂). Adsorption kinetics data show that the pseudo-second-order model fits best, with the highest regression coefficient (R² = 0.99637) found in the Cu(TAC)₂ composite, indicating a chemisorption mechanism. Adsorption equilibrium analysis using Freundlich isotherm revealed that while all materials fit the model, plain activated carbon had an unfavorable 1/n value (>1), suggesting weak interaction between adsorbent and adsorbate. Based on kinetic and isotherm analysis, the Cu(TAC)₂ composite was more effective for Fe(II) adsorption than Fe-Cu or unmodified activated carbon.